PENGARUH KOMUNIKASI, KEPERCAYAAN DAN KOMITMEN BIDAN PRAKTIK MANDIRI TERHADAP KEPUTUSAN KERJASAMA DENGAN BPJS KESEHATAN - Bernadette Teni Febriana; Anneke Suparwati; Septo Pawelas Arso (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Since the enactment of National Health Insurance (NHS) on 1th January 2014, health facilities and health workers were suggested to collaborate with NHS. However not all private practitioner midwives decided to do cooperation. Preliminary survey to 3 cooperate midwives and 3 non-cooperate midwives stated the lack of information made them assumed if cooperation was complicated. However, midwives remained to believe and committed to a cooperation. The purpose of this research was to investigate the correlation and influence between communication, trust and commitment against the cooperation decision. This type of research was observational analytic with cross sectional design. The sample of this research were 95 midwives in Semarang. Sampling techniques using simple random sampling. The research findings showed that commitment was related and leveraged midwives cooperation decision with the NHS (p = 0.00, OR = 11.739; 95% CI 3,020 – 44.484), whereas communication (0.165, p = OR = 2,069; 95% CI 0.7 – 5.8) and trust (p = 0.583, OR = 1,333; 95% CI 0.4 – 2.3) were not related to a cooperation decision. Although the decision was not influenced by communication and trust, midwives are committed to provide affordable health services to the community including NHC participants. Through this cooperation, we expected NHC UHC vision can be achieved in 2019. Communication between midwives and NHC needs to be more intensive to minimize conflict that caused by delayed of information.